Substellar objects in nearby young clusters: VII. The substellar mass function revisited - Scholz, Alexander; Geers, Vincent; Clark, Paul C.; Jayawardhana, Ray; Muzic, Koraljka (The astrophysical journal, 2013)
The abundance of brown dwarfs (BDs) in young clusters is a diagnostic of star formation theory. Here we revisit the issue of determining the substellar initial mass function (IMF) based on a comparison between NGC 1333 and IC348, two clusters in the Perseus star-forming region. We derive their mass distributions for a range of model isochrones, varying distances, extinction laws, and ages with comprehensive assessments of the uncertainties. We find that the choice of isochrone and other parameters have significant effects on the results, thus we caution against comparing IMFs obtained using different approaches. For NGC 1333, we find that the star/BD ratio R is between 1.9 and 2.4 for all plausible scenarios, consistent with our previous work. For IC348, R is found to be between 2.9 and 4.0, suggesting that previous studies have overestimated this value. Thus the star-forming process generates about 2.5-5 substellar objects per 10 stars. The derived star/BD ratios correspond to a slope of the power-law mass function of α = 0.7-1.0 for the 0.03-1.0 M☉ mass range. The median mass in these clusters—the typical stellar mass—is between 0.13 and 0.30 M☉. Assuming that NGC 1333 is at a shorter distance than IC348, we find a significant difference in the cumulative distribution of masses between the two clusters, resulting from an overabundance of very low mass objects in NGC 1333. Gaia astrometry will constrain the cluster distances better and will lead to a more definitive conclusion. Furthermore, the star/BD ratio is somewhat larger in IC348 compared with NGC 1333, although this difference is still within the margins of error. Our results indicate that environments with higher object density may produce a larger fraction of very low mass objects, in line with predictions for BD formation through gravitational fragmentation of filaments falling into a cluster potential.